PENDAMPINGAN STRATEGI BERSAING UMKM “STASIUN ES 88” MELALUI DIGITAL MARKETING DAN DIVERSIFIKASI MENU - Pariyono, Pariyono; Amin, Moh. Solikul; Syamsudin, Amin; Listiani, Nur (Fokus ABDIMAS, 2025)
This community service initiative aims to enhance the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) by addressing key challenges identified through SWOT analysis, interviews, and field observations. The objectives are: (1) to improve the visual appeal of the sales point, (2) to increase consumer awareness of the business location, (3) to establish a digital presence via social media, and (4) to diversify product offerings, including nighttime beverage options. The novelty of this program lies in its integrated approach simultaneously tackling branding, digital marketing, and product innovation to foster MSME resilience in a competitive market environment. By providing MSMEs with practical tools such as signage (banners and neon boxes), Google Maps integration, and social media accounts (Facebook, Instagram, TikTok), alongside product diversification strategies, the program offers a scalable model for MSME development. The scope of the research includes the design, implementation, and evaluation of targeted interventions aimed at improving marketing performance and product attractiveness. This study is confined to a selected MSME unit and serves as a pilot model that can be adapted to similar business contexts.